THE EFFECT OF CHICKEN MANURE AND K FERTILIZER ON GROWTH AND YIELD OF Allium chinense ON ALLUVIAL SOIL - arsenius, karlo; Faperta, Warganda; Budi, Setia (Jurnal Sains Pertanian Equator, 2019)
Indonesia has potential and prospects for developing the onion crop commodities show that a positive side of development, such as shallots and scallion commodity. Onion plants are one of the commodities that are intensively developed in West Kalimantan, one of the land used for cultivating this plant is alluvial soil. This research aims to determined the interaction between chicken manure and K fertilizer on the growth and yield of Allium chinense on alluvial soil. This research use a factorial completely randomized design (CRD). The first factor was chicken manure (p) which consisted of three levels treatment that is, p1 = 10% weight of the soil equivalent to 800 g perpolybag, p2 = 20% weight of the soil equivalent to 1600 g perpolybag, and p3 = 30% weight of the soil equivalent to 2400 g perpolybag. Second factor is K fertilizer (k) which consists of three treatment levels, that is k1 = 175 kg / ha equivalent to 0.7 g perpolybag, k2 = 200 kg / ha equivalent to 0.8 g perpolybag and k3 = 225 kg / ha equivalent 0.9 g perpoly bag. The addictional observation variables in this research were plant height (cm), number of leaves (strands), number of tillers (fruit), number of tubers (fruit), plant wet weight (g) and plant dry weight (g). The results showed that the main factors of manure significantly affected the observation variables of plant height, number of leaves and plant wet weight. The factor of both K fertilizer and interaction of chicken manure and K fertilizer had no significant effect on all observation variables. Keywords: Allium chinense, Alluvial Soil ,Chicken manure, K Fertilizer.